Biosynthesis of sphingolipids with very-long-chain pufa a hallmark of differentiating male germ cells - Oresti, Gerardo Martin (2019)
The sphingomyelins (SM) and ceramides (Cer) of rodent spermatogenic cells contain very-long-chain (C28-C32) polyenoic fatty acids (VLCPUFA), in non-hydroxy (n-V) and 2-hydroxy (h-V) forms. The SM and Cer species with n-V, present in meiotic spermatocytes, become in part h-V species in post-meiotic spermatids. In each of these cells, the mentioned species are located in the non-raft fraction of the plasma membrane. The enzymes required for PUFA elongation to n-V, Elovl5, Elovl2 and Elovl4, and the fatty acid 2-hydroxylase (Fa2h) that converts n-V to h-V, are expressed in germ cells, with Elovl4 and Fa2h protein levels being highest in spermatocytes and spermatids, respectively. The Cer and SM species with n-V and h-V are biosynthesized de novo in a germ cell type-specific and steroid hormone-dependent manner. CerS3, which specifically N-acylates VLCPUFA to sphinganine, is highly expressed in meiotic cells. The Elovl4 and CerS3 protein expression prevails in spermatocytes, is seminiferous stage-specific, and is mostly concomitant. In spermatids, the Fa2h protein appears concentrated in late stages, especially when they elongate and their heads change shape. The unique sphingolipid species with n-V and h-V, as well as the enzymes involved in their biosynthesis, are useful biomarkers for investigating normal and pathological aspects of germ and sperm cell functions. Supported by SGCyT UNS-PGI-UNS (24/B272 to GMO and 24/B218 to MIA), FONCyT (PICT2017-2535 to GMO).